PENGEMBANGAN E-MODUL BERBASIS PMRI PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMPIT AN-NIDA’ LUBUKLINGGAU - Dewi Safitri; Rani Refianti; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to develop PMRI-based e-modules on class VIII SMPIT An-Nida' Lubuklinggau flat sided geometric material that is valid, practical and has potential effects. The development model used is ADDIE. Collection techniques were carried out by interviews, filling out questionnaires, and learning achievement tests. Based on this study, the results obtained were (1) the quality of learning media seen from the aspect of language validity was 0.8 including the valid category, the media validity aspect was 0.73 included in the valid category, and the material validity aspect was 0.82 including the very valid category; (2) The quality of the media seen from the practical aspect based on the teacher's response of 87.5% is included in the very practical category, the student response (one to one) is 83.3% included in the very practical category, and the student response (small group) is 90% included in the very practical category; (3) Learning media has a potential effect on student learning outcomes, as many as 20 students (76.92%) are included in the complete category and 6 (23.07%) have not completed the KKM set by the school at 70. The potential effect of this learning media is categorized as good.